Direct oral anticoagulant drug level testing in clinical practice: A single institution experience. Issue 143 (July 2016) - Martin, Karlyn; Moll, Stephan
Abstract: We performed a review of all direct oral anticoagulant (DOAC) levels – ecarin times for dabigatran and anti-Xa levels for rivaroxaban and apixaban – ordered at our institution with the purpose of evaluating DOAC levels from "real-world" (non-clinical trial) patients taking DOACs long-term, in order to assess levels obtained, reasons for checking levels, and actions taken based on the testing result. A total of 28 patients had 48 levels sent over a 36-month period. The majority of outpatient levels were within or close to the range of published values. The setting in which levels were sent influenced how results affected management decisions: in the outpatient setting, the majority of levels served to reassure clinicians that DOAC levels were within expected ranges resulting in continuation of chosen management, whereas in the inpatient setting, DOAC levels were used most frequently to detect DOAC presence in urgent clinical situations and influenced clinical decision-making in the peri-procedural and pre-operative periods. Our results demonstrate that while testing may be useful if immediately available in urgent clinical situations where assessment of drug presence is needed, DOAC level monitoring is infrequently used overall, and the lack of use combined with the paucity of available evidence to guide clinical decision-making based on the results suggests there is little urgency to make the tests widely available for routine use outside of acute settings in the emergency department and urgent surgical setting. Highlights: DOAC testing results from patients taking anticoagulation long-term are presented. Reasons for testing and clinical consequences of DOAC level results are explored. DOAC level testing is infrequently used at our institution.